2017
DOI: 10.3345/kjp.2017.60.5.129
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors and treatment of pediatric acute lymphoblastic leukemia

Abstract: The event-free survival (EFS) for pediatric acute lymphoblastic leukemia (ALL) has shown remarkable improvement in the past several decades. In Korea also, a recent study showed 10-year EFS of 78.5%. Much of the improved outcome for pediatric ALL stems from the accurate identification of prognostic factors, the designation of risk group based on these factors, and treatment of appropriate duration and intensity according to risk group, done within the setting of cooperative clinical trials. The schema of first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
49
0
11

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(64 citation statements)
references
References 81 publications
4
49
0
11
Order By: Relevance
“…Specific high‐risk subgroups, such as the molecular genetic abnormality, that is Philadelphia chromosome‐positive acute lymphoblastic leukaemia, continue to have significantly lower survival rates than other ALL children. Ph+ ALL was associated with a high relapse rate when treated with chemotherapy alone . Hematopoietic stem cell transplant (HSCT) was considered the therapy of choice, notably when a matched sibling donor (MSD) was available .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specific high‐risk subgroups, such as the molecular genetic abnormality, that is Philadelphia chromosome‐positive acute lymphoblastic leukaemia, continue to have significantly lower survival rates than other ALL children. Ph+ ALL was associated with a high relapse rate when treated with chemotherapy alone . Hematopoietic stem cell transplant (HSCT) was considered the therapy of choice, notably when a matched sibling donor (MSD) was available .…”
Section: Discussionmentioning
confidence: 99%
“…Ph+ ALL was associated with a high relapse rate when treated with chemotherapy alone. 12,13 Hematopoietic stem cell transplant (HSCT) was considered the therapy of choice, notably when a matched sibling donor (MSD) was available. 14 However, recent data have indicated that chemotherapy used together with tyrosine kinase inhibitor (TKI) may be an alternative effective therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Acute lymphoblastic leukemia (ALL) is the most common cancer among pediatric and adolescent patients, and it accounts for major cancer-related deaths in childhood. 1) Various factors, including exogenous (e.g., infection) or endogenous exposures (e.g., inflammation, oxidative stress) and genetic background, contribute to disease onset; ALL occurs in roughly 1:2,000 children aged <15 years. 2) After successful evolution of chemotherapy and clinical trials spanning 5 decades, the current curability rate of ALL is approximately 90% in resource-rich countries.…”
Section: Introductionmentioning
confidence: 99%
“…ALL can also occur in adults, although less frequently, and the prognosis is far less favorable, with frequent relapse. 1 There are several factors responsible for the poor outcome of ALL in adults, including comorbidities, poor performance status, poor compliance, and higher frequency of high-risk genomic subgroups. 1 Philadelphia (Ph)-positive chromosome is a genetic translocation between chromosomes 9 and 22 that causes the production of a BCR-ABL1 fusion gene.…”
Section: Introductionmentioning
confidence: 99%